2022
DOI: 10.56938/rceem.v1i1.3168
|View full text |Cite
|
Sign up to set email alerts
|

As relações entre a Sequência Fedathi aplicada no ensino de Matemática e o Pensamento Matemático Avançado

Abstract: As discussões em torno do ensino de Matemática são constantes e se debruçam sobre as didáticas específicas para essa área. Estudiosos do campo da Educação Matemática buscam elaborar estratégias e metodologias com o intuito de melhorar o processo de ensino e de aprendizagem matemática, focando nos processos de construção do conhecimento. Nessa perspectiva, destacam-se a metodologia de ensino Sequência Fedathi e a teoria do Pensamento Matemático Avançado. A primeira, com foco na atuação docente, transpõe o métod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…In 1888, Appell [2] studied a class of oriented surfaces in R 3 associated with a area preserving transformation on the sphere. Later, Ferreira and Roitman [10] found that these surfaces satisfy the Weingarten relation H + Ψ ν K = 0, for a fixed point ν ∈ R 3 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In 1888, Appell [2] studied a class of oriented surfaces in R 3 associated with a area preserving transformation on the sphere. Later, Ferreira and Roitman [10] found that these surfaces satisfy the Weingarten relation H + Ψ ν K = 0, for a fixed point ν ∈ R 3 .…”
Section: Introductionmentioning
confidence: 97%
“…Weierstrass first obtained this representation locally in 1866, and its crucial aspect is providing a method for defining numerous examples of minimal surfaces. One version of this representation can be found in [3].…”
Section: Introductionmentioning
confidence: 99%